Pengembangan Game Edukasi Pengenalan Pakaian Adat Bali Berbasis Android - Adi Saputra, Kadek Surya; Pradipta, I Made; Chrisniyanti, Ayu; Krisnawan, Gusti Ngurah Aditya; Upadani, I Gusti Ayu Widari (LPPM UNIKA Santo Thomas, 2023)
The rapid development of technology today accompanied by the influence of foreign cultures, makes today's younger generation less interested in learning and preserving their culture, especially about Balinese traditional clothing culture. With the application of technology, we can anticipate by creating interactive educational media that can be delivered to its users. The development of this educational media can be applied in the Android-based Balinese traditional clothing introduction game application, which provides knowledge to users in getting to know the types of traditional clothing, especially in the Bali area in an innovative and interactive way. The method used in making this application is the Multimedia Development Life Cycle (MDLC). This learning media testing stage uses the black-box testing method which is used to observe the execution results through test result data that focuses on the requirements and functionality of the application made. The results of this research are expected to increase public interest, especially in the younger generation, to preserve Balinese art and culture. Keywords: Educational Games, Balinese Traditional Clothing, Multimedia Applications